Subtropical cyclones over the oceanic basins: a review - Rocha, Rosmeri Porfirio da; Reboita, Michelle Simoes; Gozzo, Luiz Felippe [UNESP]; Mosso Dutra, Livia Marcia; Jesus, Eduardo Marcos de (Wiley-Blackwell, 2019)
Subtropical cyclones are hybrid systems presenting a warm core at low levels, as tropical cyclones, and a cold core at upper levels, as extratropical cyclones. Their genesis can be as proper subtropical system or from the transitions (extratropical to subtropical or tropical to subtropical). Subtropical cyclones occur mostly over the sea and generate intense near surface winds with great impacts on human activities and ecosystems. We present a review of the main features, as obtained from observations and numerical simulations, for subtropical cyclone development over the major oceanic basins.
Keywords: subtropical cyclones; oceanic basins; cyclone trends; synoptic and dynamic features; numerical simulations